The Effectiveness of Parent Skills Training on Attitudes Toward Addiction and Sensation Seeking in Male Lower Secondary School Students in Borujerd - Rahdar, Habibollah; Taghvaei, Davood; Pirani, Zabihollah (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to examine the effectiveness of parent skills training on attitudes toward addiction and sensation seeking among male lower secondary school students in Borujerd. Methods and Materials: The study employed an applied, quasi-experimental design with a pretest–posttest nonequivalent control group. The statistical population included male students aged 13–15 years enrolled in lower secondary schools in District 1 of Borujerd during the 2019–2020 academic year and their mothers. Following a two-stage screening process based on elevated scores in attitudes toward addiction and sensation seeking, 60 students were selected and randomly assigned to experimental and control groups. The intervention consisted of an eight-session, 90-minute parent skills training program delivered to mothers in the experimental group, grounded in communication- and family-systems principles. The control group received no intervention during the study period. Data were collected at pretest and posttest using standardized self-report measures assessing attitudes toward addiction and sensation seeking. Data were analyzed using analysis of covariance (ANCOVA) to control for baseline differences. Findings: After controlling for pretest scores, ANCOVA results indicated a significant group effect on positive attitudes toward addiction (F = 29.11, p < .001, partial η² = .34) and negative attitudes toward addiction (F = 25.04, p < .001, partial η² = .31), demonstrating meaningful posttest differences between the experimental and control groups. Additionally, a significant group effect was observed for sensation seeking (F = 35.10, p < .001, partial η² = .38), indicating a substantial reduction in sensation seeking among students whose parents participated in the training program. Conclusion: Parent skills training was effective in improving adolescents’ attitudes toward addiction and reducing sensation seeking, highlighting the critical role of parent-focused interventions in preventing psychological risk factors associated with substance use during early adolescence.